Exposure of two Eutrema salsugineum (Thellungiella salsuginea) accessions to water deficits reveals different coping strategies in response to drought. Issue 3 (19th January 2015) - MacLeod, Mitchell J.R.; Dedrick, Jeff; Ashton, Claire; Sung, Wilson W.L.; Champigny, Marc J.; Weretilnyk, Elizabeth A.
<x xml:space="preserve">Abstract</x> Eutrema salsugineum is an extremophile related to Arabidopsis. Accessions from Yukon, Canada and Shandong, China, were evaluated for their tolerance to water deficits. Plants were exposed to two periods of water deficit separated by an interval of re‐watering and recovery. All plants took the same time to wilt during the first drought exposure but Yukon plants took 1 day longer than Shandong plants following the second drought treatment. Following re‐watering and turgor recovery, solute potentials of Shandong leaves returned to predrought values while those of Yukon leaves were lower than predrought levels consistent with having undergone osmotic adjustment. Polar metabolites profiled in re‐watered plants showed that different metabolites are accumulated by Yukon and Shandong plants recovering from a water deficit with glucose more abundant in Yukon and fructose in Shandong leaves. The drought‐responsive expression of dehydrin genes RAB18, ERD1, RD29A and RD22 showed greater changes in transcript abundance in Yukon relative to Shandong leaves during both water deficits and recovery with the greatest difference in expression appearing during the second drought. We propose that the initial exposure of Yukon plants to drought renders them more resilient to water loss during a subsequent water deficit leading to delayed wilting. Yukon plants also established a high leaf water content and increased specific leaf area during the second deficit. Shandong plants undergoing the same treatment regime do not show the same beneficial drought tolerance responses and likely use drought avoidance to cope with water deficits.